2011
DOI: 10.1029/2010rs004566
|View full text |Cite
|
Sign up to set email alerts
|

A short note on the assimilation of collocated and concurrent GPS and ionosonde data into the Electron Density Assimilative Model

Abstract: [1] The Electron Density Assimilative Model (EDAM) has been developed to provide real-time characterizations of the ionosphere by assimilating diverse data sets into a background model. Techniques have been developed to assimilate virtual height ionogram traces rather than relying on true height inversions. A test assimilation has been conducted using both GPS and ionosonde data as input. Postassimilation analysis shows that foF2 residuals can be degraded when only GPS data are assimilated. It has also been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…A comprehensive specification of the ionosphere in terms of electron density, neutral particles-electrons collision frequency, and geomagnetic field is required in order to carry out an accurate ray-tracing. Therefore, when dealing with near real-time applications of ray-tracing, it is of crucial importance to have a realistic ionospheric modelling through 3-D models of ionospheric electron density, which after assimilating measured data calculate an updated 3-D image of the ionosphere (Angling and Khattatov, 2006;Thompson et al, 2006;Fridman et al, 2006Fridman et al, , 2009Decker and McNamara, 2007;McNamara et al, 2007McNamara et al, , 2008McNamara et al, , 2010McNamara et al, , 2011McNamara et al, , 2013Angling and Jackson-Booth, 2011;Shim et al, 2011). More recently, at the INGV, the IRI-SIRMUP-PROFILES (ISP) model, capable of providing a 3-D electron density profile representation of the ionosphere in quasi real time, was developed.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive specification of the ionosphere in terms of electron density, neutral particles-electrons collision frequency, and geomagnetic field is required in order to carry out an accurate ray-tracing. Therefore, when dealing with near real-time applications of ray-tracing, it is of crucial importance to have a realistic ionospheric modelling through 3-D models of ionospheric electron density, which after assimilating measured data calculate an updated 3-D image of the ionosphere (Angling and Khattatov, 2006;Thompson et al, 2006;Fridman et al, 2006Fridman et al, , 2009Decker and McNamara, 2007;McNamara et al, 2007McNamara et al, , 2008McNamara et al, , 2010McNamara et al, , 2011McNamara et al, , 2013Angling and Jackson-Booth, 2011;Shim et al, 2011). More recently, at the INGV, the IRI-SIRMUP-PROFILES (ISP) model, capable of providing a 3-D electron density profile representation of the ionosphere in quasi real time, was developed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (e.g. Angling and Jackson-Booth, 2011;Feltens et al, 2011) have shown that EDAM can accurately represent the ionosphere using GNSS data.…”
Section: The Electron Density Assimilative Model (Edam)mentioning
confidence: 99%
“…Additional electric field measurements provide an enhanced data base compared to former LEO satellites like CHAMP and Ørsted. Amm et al (2013) propose the application of the SECS method to solve for the ionospheric and field-aligned current systems. Derived electric currents and the electric field observations are then applied to solve Ohm's law for the electro-dayamics of the ionosphere resulting in maps of conductance and plasma convection along the location of the Swarm orbits.…”
Section: Swarm Data As a Tool For Novel Satellite-based Space Weathermentioning
confidence: 99%